Nitrile-aminothiol bioorthogonal near-infrared fluorogenic probes for ultrasensitive in vivo imaging - Weiping Xu; Shujuan Yi; Jie Liu; Yuyan Jiang; Jiaguo Huang (Nature Communications)
Abstract Bioorthogonal chemistry-mediated self-assembly holds great promise for dynamic molecular imaging in living organisms. However, existing approaches are limited to nanoaggregates with ‘always-on’ signals, suffering from high signal-to-background ratio (SBR) and compromised detection sensitivity. Herein we report a nitrile-aminothiol (NAT) bioorthogonal fluorogenic probe (CyNA P -SS-FK) for ultrasensitive diagnosis of orthotopic hepatocellular carcinoma. This probe comprises a nitrile-substituted hemicyanine scaffold with a cysteine tail dually locked with biomarker-responsive moieties. Upon dual cleavage by tumor-specific cathepsin B and biothiols, the 1,2-aminothiol residue is exposed and spontaneously reacts with nitrile group for in situ intramolecular macrocyclization, enabling near-infrared fluorescence (NIRF) turn-on as well as self-assembly. In living male mice, such ‘cleavage-click-assembly’ regimen allows for real-time and ultrasensitive detection of small cancerous lesions (~2 mm in diameter) with improved SBR (~5) and extended detection window (~36 h), outperforming conventional clinical assays. This study not only presents NAT click reaction-based fluorogenic probes but also highlights a generic dual-locked design of these probes.